Party Crashers: Issues in Identifying Parties and Others Bound by Arbitration Agreements - Allison, Simon; Dharmananda SC, Kanaga (Oxford University Press, 2022)
The determination of the law governing arbitration agreements has been the subject of recent close attention. The relationship of third parties to arbitration agreements is sensitive to an increasingly unwieldly array of factors, including the subject matter of a dispute, the nature of the purported basis for the transfer of an arbitration agreement, and the wording of the original instrument containing the arbitration clause. A rising question is whether third parties are to be considered parties or non-parties otherwise bound by arbitration agreements. In addition, there is an issue of timing: when are the arbitration agreements or relevant awards to be impugned, and does the third-party issue pertain to the validity or just the scope of an arbitration agreement. This article seeks to address these issues.